A PREDICTION MODEL FOR CHRONIC HEART FAILURE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Mariia Yu. Koteliukh; Svitlana I. Bokova; Nadiia V. Demikhova; Nataliia D. Lantukhova (Клінічна та профілактична медицина)
Introduction. One of the common adverse complications that may occur in patients with type 2 diabetes mellitus (T2DM) after acute myocardial infarction (AMI) is the development and progression of chronic heart failure (CHF). Currently, it remains relevant to study biomarkers of energy homeostasis that are involved in the pathogenesis of CHF in T2DM patients.